2018
DOI: 10.1007/s00415-018-8850-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal cognitive biomarkers predicting symptom onset in presymptomatic frontotemporal dementia

Abstract: IntroductionWe performed 4-year follow-up neuropsychological assessment to investigate cognitive decline and the prognostic abilities from presymptomatic to symptomatic familial frontotemporal dementia (FTD).MethodsPresymptomatic MAPT (n = 15) and GRN mutation carriers (n = 31), and healthy controls (n = 39) underwent neuropsychological assessment every 2 years. Eight mutation carriers (5 MAPT, 3 GRN) became symptomatic. We investigated cognitive decline with multilevel regression modeling; the prognostic perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
71
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 54 publications
11
71
3
Order By: Relevance
“…MAPT mutation carriers were the only group impaired on both immediate and delayed recall at baseline, whereas GRN and C9orf72 mutation carriers were only impaired on immediate recall. This is in line with a previous study by Jiskoot et al [16] that demonstrated significant decline on the RAVLT recall test in the presymptomatic stage of MAPT mutation carriers, with a further decline in participants that converted to symptomatic FTD during follow-up. This is further corroborated by the finding that the RBMT direct and delayed recall trials were most sensitive to differentiate MAPT mutation carriers from non-carriers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…MAPT mutation carriers were the only group impaired on both immediate and delayed recall at baseline, whereas GRN and C9orf72 mutation carriers were only impaired on immediate recall. This is in line with a previous study by Jiskoot et al [16] that demonstrated significant decline on the RAVLT recall test in the presymptomatic stage of MAPT mutation carriers, with a further decline in participants that converted to symptomatic FTD during follow-up. This is further corroborated by the finding that the RBMT direct and delayed recall trials were most sensitive to differentiate MAPT mutation carriers from non-carriers.…”
Section: Discussionsupporting
confidence: 93%
“…The most profound decline was seen on attention/mental processing speed and memory. Memory problems have previously been described in GRN as a symptom characterizing progressed disease stages [16], although it could also be associated with the profound impairment in attention/mental processing speed [31].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This might suggest that additional frontal executive function in aMCI increases risk for AD rather than FTD. However, since frontal-executive dysfunction is a hallmark of FTD symptomatology and FTD may have a sneaky onset 13 , it is possible that these patients may develop FTD.…”
Section: Discussionmentioning
confidence: 99%
“…However, measurable episodic memory impairment in bvFTD patients may be as severe as in the patients with AD [15,[39][40][41][42][43]. Memory deficits have also been noted in the clinical memory tests of bvFTD patients at the presymptomatic stage [44,45]. Relatively spared episodic memory is, however, considered as one of the main features suggestive for bvFTD in the prevailing diagnostic criteria [2].…”
Section: Discussionmentioning
confidence: 99%